Critical view on RNA silencing-mediated virus resistance using exogenously applied RNA - Uslu, Veli Vural; Wassenegger, Michael (Current opinion in virology, 2020)
In almost all eukaryotes, RNA interference (RNAi) is a natural defence mechanism against foreign nucleic acids, including transposons and viruses. It is generally triggered by long double stranded RNA molecules (dsRNA, >50bp) that are processed into small interfering RNAs (siRNAs). RNAi can be artificially activated by the expression of RNAi triggers through viruses (virus-induced gene silencing, VIGS) and transgenes. Moreover, for almost 10 years, exogenous RNA application methods are developed as tools to induce RNAi in plants. In this review, exogenous RNA application techniques having the potential to activate RNAi with a focus on RNAi-mediated virus resistance will be discussed. Limitations of exogenous RNA applications, targeting of virus vectors and open questions related to mechanistic details that still require further investigation will be pointed out.
Gesehen am 26.10.2020